2010
DOI: 10.1002/micr.20727
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of contractile function recovery with acetylcholine receptor changes in a rat muscle flap model

Abstract: The aim of this study was to investigate the correlation between contractile function recovery and changes of acetylcholine receptors (AChR) in a transferred muscle flap following reinnervation. Orthotopic transfer of the gracilis muscle flap with repair of its nerve was performed bilaterally in 48 rats. The rats were randomly divided into six experimental groups based on the time intervals for assessments (1, 4, 5, 10, 20, and 30 weeks). Sixteen gracilis muscle samples from eight rats without surgery were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We also noted a nearly 60 % decrease in AChR ε subunit in Sarco soleus muscle, which contrasts with the increase in AChR ε that was seen in VO rat muscle. In this respect, previous studies have shown that following denervation AChR ε expression undergoes a multiphasic response: (i) an initial decrease in the first 10 day post-denervation [29]; (ii) a sharp increase observed approximately 4 weeks following denervation; (iii) a decline over the next 4 weeks; and (iv) a gradual secondary increase when denervation persists beyond 2 months [30, 31]. Thus, the differences between the VO rat and Sarco mouse likely reflect differences in the duration of denervation, with the higher AChR ε in VO rat reflecting more prolonged denervation and the reduced AChR ε in Sarco mouse reflecting the acute denervation response.…”
Section: Discussionmentioning
confidence: 99%
“…We also noted a nearly 60 % decrease in AChR ε subunit in Sarco soleus muscle, which contrasts with the increase in AChR ε that was seen in VO rat muscle. In this respect, previous studies have shown that following denervation AChR ε expression undergoes a multiphasic response: (i) an initial decrease in the first 10 day post-denervation [29]; (ii) a sharp increase observed approximately 4 weeks following denervation; (iii) a decline over the next 4 weeks; and (iv) a gradual secondary increase when denervation persists beyond 2 months [30, 31]. Thus, the differences between the VO rat and Sarco mouse likely reflect differences in the duration of denervation, with the higher AChR ε in VO rat reflecting more prolonged denervation and the reduced AChR ε in Sarco mouse reflecting the acute denervation response.…”
Section: Discussionmentioning
confidence: 99%
“…A well-established tool to achieve this goal is the AV-loop model [31, 32]. However, to gain functional muscle tissue, besides axial vascularization, an innervation by a motor nerve seems indispensable [22]. In the past mainly myoblasts or satellite cells have been used for skeletal muscle TE, but they showed limited cell survival in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, this single study only allowed the use of a sensoric nerve [20]. Agrawal and Zhang and coworkers study the dependence of motoric innervation in the context of muscle regeneration and motoric neurotization in transplanted muscle flaps [21, 22]. Neurotization can be a stimulus to activate mechanisms of muscle differentiation and contraction.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…The effect of nerve coaptation (tibial nerve to a branch of the obturator nerve as described in the EPI-loop model [ 30 ]) would be the next step to analyze. Zhang et al performed orthotopic transplantation of rat gracilis muscle with transection of the obturator nerve and subsequent neurorrhaphy of the nerve [ 31 ]. After 5–20 weeks after reinnervation, muscle function started to recover.…”
Section: Discussionmentioning
confidence: 99%